What do you mean by the term "ethnography"? - Delamont, Sara, 1947- ([Thousand Oaks, Calif. : SAGE], 2009)
The speaker prefers as her main understanding of the word "ethnography" the idea of something driven by observation but accompanied by other methods of research such as collection of documents, online research, etc.
"SAGE research methods online."
Title from home page (viewed Jan. 26, 2011).
Online video.
Includes transcript.
Specialized.
Mode of access: World Wide Web.
Keywords: elektronické knihy; electronic books; Ethnography -- Methodology